The investigation of incidence and radiological findings of gastrointestinal stromal tumor as a rare cause of abdominal mass - Koç, Mustafa; Serhatlioğlu, Selami (My University, 2017)
Aim: The aim of the present study was to evaluate the investigation of incidence and radiological findings of gastrointestinal stromal tumors (GIST) as a rare cause of abdominal mass, with current literature review.Material and Methods: Between February 2011 and May 2016, a total of 4,443 patients who underwent abdominal multislice computed tomography and magnetic resonance imaging due to the clinical indications for abdominal pain, abdominal swelling-mass were analyzed in our hospital. The retrospective cross-sectional study included forty-five patients, who were subsequently diagnosed with GIST histopathologically. Results: GIST was identified in 45 (1%) patients. Of the total 45 patients, 21 (47%) were men and 24 (53%) were female. The mean age was 55 years, ranging from 35 to 73 years. As a result of radiological examinations, the tumor location was stomach in 22 cases (49%), small intestine in 12 cases (27%) and colon in 9 cases (20%). The retroperitoneal localization was also found in 2 cases (4%). The average size of the lesions ranged between 2 and 15 cm. Malignant degeneration and omental metastasis were seen in 11 (24%) and 7 cases (16%) respectively.Conclusion: GIST is a rare cause of abdominal mass with an incidence of 1% in our region. They are most commonly localized in the stomach, rarely in the omentum/mesentery and retroperitoneum. The Malignant transformation is not frequent. Diagnosis and evaluations of mass can be made successfully by radiological imaging modalities.
Keywords: Genel ve Dahili Tıp; Onkoloji